New method for the synthesis of chromeno[4,3-b]chromene derivatives via multicomponent reaction promoted by niobium pentachloride - dos Santos, Willian Henrique [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Elsevier, 2017)
Chromeno[4,3-b]chromene derivatives were synthesized from multicomponent reaction between 4-hydroxycoumarin, aryl aldehyde derivatives and 1,3-cyclohexanedione promoted by niobium pentachloride. This new method is simple, cost-effective, provides good yields with good substrate generality and can be conducted in short reaction times.
Keywords: Chromene; Coumarin; Lewis acid; Multicomponent reactions; Niobium pentachloride